Serum Anti-SARS-CoV-2 IgG in Chronic Hepatitis B Virus Positive Patients - Mazumder , Mohammad Mahadi Hasan; Begum, Ifat Ara; Alam, Mohammad Nurul; Hossain, Mohammed Khaled Mosharraf; Gulshan , Masrufa; Akter, Nargis; Kaisar, Sahidullah (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Advanced age and comorbidities such as diabetes mellitus, hypertension, chronic obstructive pulmonary disease or cardiovascular diseases are proven risk factors in COVID-19. In COVID-19, pre-existing liver illnesses could be a substantial risk factor for hospitalization and severity. Infection with the hepatitis B virus (HBV) is one of the most significant and common health disorders. Objective: To estimate serum anti-SARS-CoV-2 IgG in chronic Hepatitis B virus positive patients. Methodology: This cross-sectional analytical study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka, during the period of January 2021 to December 2021. A total of 63 subjects were selected from Hepatology Department of DMCH and BSMMU as per selection criteria. Among them, 23 were chronic HBV positive patients (3 with COVID-19 and 20 without COVID-19) (group A) and the rest 40 were non HBV cases (20 with COVID-19 and 20 without COVID-19) (group B). Blood sample was collected for the measurement of anti-SARS-CoV-2 IgG. Biochemical analysis was performed by chemiluminescent microparticle immunoassay (CMIA) in the Department of Biochemistry, BSMMU, Dhaka. Result: In this study, the mean age of group A was 47.26 ± 11.24 years and group B was 44.53 ± 10.17 years. Males were predominant in both the groups. In group A, male was 65.2% & female was 34.8% and in group B, male was 60% & female was 40%. The median value of serum anti-SARS-CoV-2 IgG level was 1110.70 in group A and 417.85 in group B (p>0.05). The study showed frequency of positivity of serum anti-SARS-CoV-2 IgG level in COVID-19 positive cases was 95.7% and in COVID-19 negative cases it was 90%. In this study, the median value of serum anti-SARS-CoV-2 IgG level significantly higher in COVID-19 positive (1063.20) than in COVID-19 negative (119.00) in non-HBV cases. Conclusion: Serum anti-SARS-CoV-2 IgG level was non-significantly higher in chronic HBV positive patients than non-HBV patients. J Com Med Col Teachers Asso Jan 2024; 28(1): 19-23